PENGARUH MOTIVASI BELAJAR DAN PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS: (Survey Pada Siswa Kelas X SMK Swasta di Kecamatan Parungpanjang Bogor) - Akhmad Kharis Kurniawan; Puput Ratna Julaeha (LPPM Institut Nida El-Adabi, 2023)
This study is aimed to determine the effect of learning motivation and vocabulary mastery on students' English speaking skills. The research method used is the survey method. A sample of 95 students was selected by using proportional random sampling technique. Data collection is done by distributing questionnaires and tests. Data analysis with descriptive statistical methods and regression. The results showed that; (1) There is a significant effect of learning motivation and vocabulary mastery together on the ability to speak English. This is evidenced by the acquisition of the value of Sig. 0.000 < 0.05 and Fh = 16.525. Together, the variables of learning motivation and vocabulary mastery contributed 26.4% to the ability to speak English; (2) There is a significant effect of learning motivation on the ability to speak English. This is evidenced by the acquisition of the value of Sig. 0.001<0.05 and tcount = 3.563 and. The variable of learning motivation contributed 12.74% in improving the ability to speak English; and (3) There is a significant effect of vocabulary mastery on the ability to speak English. This is evidenced by the acquisition of the value of Sig. 0.000 < 0.05 and tcount = 3.716. Vocabulary mastery variable contributes 13.66% in improving English speaking skill.